Strategic brand management based on sustainable-oriented view: an evaluation in Turkish home appliance industry - (:unkn) unknown (ELSEVIER SCIENCE BV, 2013)
This paper evaluates the effect of firm sustainability on brand perception, which is key to brand image in brand management and marketing. The paper also reviews the literature in understanding well-established activities of sustainability effecting brand perception of individuals. Branding literature explains the influence of a brand on sustainability-driven opportunities available to a firm for brand image. The objective of this study is to explore how sustainability-based brand image making of managers effective in driving opportunities available to a firm for marketing performance. A conceptual framework grounded in this study is based on the sustainability-based brand image that effects marketing performance of a brand sold through retailers and customers which in turn can create numerous opportunities for marketing. A descriptive qualitative survey exploring sustainability activities of three big brands in home appliances industry in Turkey has been included in the study. The results indicated that the model developed by using existing approaches in the literature, provides supportive findings for further large scale empirical investigations in terms of variables and hypotheses that can be used for both academic and managerial purposes. In future studies, relationship between sustainability and brand image and marketing performance can be evaluated within wider perspectives.
Keywords: sustainable; sustainability; brand image; brand management; Turkish home appliance industry; CORPORATE SOCIAL-RESPONSIBILITY; SERVICE; EQUITY